INDIA'S MIGRANT WORKERS AND THE PANDEMIC - Bandyopadhyay, Ritajyoti; Banerjee, Paula; Samaddar, Ranabir ([S.l.] : ROUTLEDGE, 2021)
A sudden announcement was made by the government on 24 March 2020 of a complete lockdown of the country, due to the spectre of Coronavirus. India's Migrant Workers and the Pandemic was being written as the crisis was unfolding with no end in sight. Migrant workers from different parts of India had no choice but to trek back hundreds of kilometres carrying their scanty belongings and dragging their hungry and thirsty children in the scorching heat of the plains of India to reach home. How did caste, race, gender, and other fault lines operate in this governmental strategy to cope with a virus epidemic?The eight papers in this collection, highlight the ethical and political implications of the epidemic--particularly for India's migrant workers. What were the forces of power at play in this war against the epidemic? What measures could have been taken and need to be taken now? Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
Keywords: Migrant labor -- India -- Social conditions; COVID-19 Pandemic, 2020- -- Social aspects -- India